Association of Defective Regulation of Autoreactive Interleukin‐6–Producing Transitional B Lymphocytes With Disease in Patients With Systemic Sclerosis. Issue 3 (6th February 2018) - Taher, Taher E.; Ong, Voon H.; Bystrom, Jonas; Hillion, Sophie; Simon, Quentin; Denton, Christopher P.; Pers, Jacques‐Olivier; Abraham, David J.; Mageed, Rizgar A.
Abstract : Objective: Systemic sclerosis (SSc) has the highest case‐specific mortality of any rheumatic disease, and no effective therapy is available. A clear manifestation of SSc is the presence of autoantibodies. However, the origin of autoantibody‐producing B lymphocytes, their mechanisms of activation and autoantibody production, and their role remain unclear. This study was undertaken to identify mechanisms that contribute to pathogenic B cell generation and involvement in SSc and to assess the altered distribution and function of B cells in SSc patients. Methods: Multicolor flow cytometry was performed to determine B cell subset distribution, cytokine production, and tolerance induction in SSc patients and healthy controls. Cytokine production following stimulation of the cells ex vivo was determined by multiplex assay. Results: A range of defects in B lymphocyte tolerance and cytokine production in SSc were noted. There was evidence of altered distribution of transitional B cell subsets, increased production of interleukin‐6 (IL‐6) and IL‐8, and defective tolerance induction in SSc B cells. In addition, B cells from SSc patients had a reduced ability to produce IL‐10 when stimulated through innate immune pathways. In contrast to healthy individuals, tolerance checkpoints in SSc patients failed to suppress the emergence of B cells that produce autoantibodies with specificity to the Scl‐70 antigen, which is strongly associated with SSc. These defects were paralleled by altered intracellular signaling and apoptosis following B cell receptor engagement. Conclusion: Our findings provide new insights into mechanisms underlying defective B lymphocyte responses in patients with SSc and their contribution to disease.